Prognostic Utility of a Modified HEART Score When Different Troponin Cut Points Are Used. Issue 3 (12th May 2021) - Aurora, Lindsey; McCord, James; Nowak, Richard; Giannitsis, Evangelos; Christenson, Robert; DeFilippi, Christopher; Lindahl, Bertil; Christ, Michael; Body, Richard; Jacobsen, Gordon; Mueller, Christian
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Although the recommended cut point for cardiac troponin (cTn) is the 99th percentile, many institutions use cut points that are multiples higher than the 99th percentile for diagnosing acute myocardial infarction (AMI). Prior studies have shown that patients with a HEART score (HS) ≤ 3 and normal serial cTn values (modified HS) are at low risk for adverse events. This study aimed to evaluate the prognostic utility of the HS when various cTn cut points are used. Methods: This was a substudy of High Sensitivity Cardiac Troponin T assay for RAPID Rule-out of Acute Myocardial Infarction (TRAPID-AMI), a multicenter, international trial evaluating a rapid rule-out AMI study using high-sensitivity cardiac troponin T (hs-cTnT). One-thousand two-hundred eighty-two patients were evaluated for AMI from 12 centers in Europe, United States, and Australia from 2011 to 2013. Blood samples of hs-cTnT were collected at presentation and 2 hours, and each patient had a HS calculated. The US Food and Drug Administration approved 99th percentile for hs-cTnT (19 ng/L) was used. Results: There were 213 (17%) AMIs. Within 30 days, there were an additional 2 AMIs and 8 deaths. The adverse event rates at 30 days (death/AMI) for a HS ≤ 3 and nonelevated hs-cTnT over 2 hours using increasing hs-cTnT cut points ranged from 0.6% to 5.1%. Conclusions: Using the recommended 99th percentile cut point for hs-cTnT, the combination of a HS ≤ 3 with nonelevated hs-cTnT values over 2 hours identifies a low-risk cohort who can be considered for discharge from the emergency department without further testing. The prognostic utility of this strategy is greatly lessened as higher hs-cTnT cut points are used.